Egg Consumption Increases Vitamin E Absorption from Co-Consumed Raw Mixed Vegetables in Healthy Young Men(1)(2)(3) - Kim, Jung Eun (J Nutr, 2016)
Background: Most people living in the United States underconsume vitamin E, and dietary approaches to increase the absorption of vitamin E may help individuals to meet their body’s needs. Objective: We assessed the effect of adding cooked whole egg to a raw mixed-vegetable salad on α-tocopherol and γ-tocopherol absorption. Methods: With the use of a randomized-crossover design, 16 healthy young men [mean ± SD age: 24 ± 4 y; mean ± SD body mass index (in kg/m(2)): 24 ± 2] consumed the same salad (all served with 3 g canola oil) with no egg [control (CON)], with 75 g cooked egg [low egg (LE)], or with 150 g cooked egg [high egg (HE)]; a 1-wk dietary washout period was included between trials. For the first 7 d of each trial, participants consumed a low–vitamin E diet to reduce plasma vitamin E concentrations. Blood was collected hourly for 10 h and the triacylglycerol-rich lipoprotein fractions (TRLs) were isolated. α-Tocopherol and γ-tocopherol concentrations in TRLs were analyzed and composite areas under the curve (AUCs) were calculated. Results: The α-tocopherol 0- to 10-h AUCs (AUCs(0–10 h)) in TRLs was higher (P < 0.05) for the HE trial (least-squares mean ± SE: 981 ± 162 nmol/L ⋅ 10 h) than for the LE (311 ± 162 nmol/L ⋅ 10 h) and CON (117 ± 162 nmol/L ⋅10 h) trials, which did not differ from one another. The γ-tocopherol AUCs(0–10 h) in TRLs was also higher (P < 0.05) for the HE trial (402 ± 54 nmol/L ⋅ 10 h) than for the CON trial (72 ± 54 nmol/L ⋅ 10 h). Conclusion: The consumption of cooked whole eggs is an effective way to increase the absorption of α-tocopherol and γ-tocopherol from a co-consumed meal that naturally contains vitamin E, such as a raw mixed-vegetable salad, in healthy young men. This trial was registered at clinicaltrials.gov as NCT01951313.